How Germany and France could play a leading role in international donor coordination - Lennart Kaplan (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
The future shape of European trade policy and the right stance to take in security and climate matters are currently the subject of fierce Franco-German debate. These issues are also relevant to development policy in the context of the overarching 2030 Agenda for Sustainable Development. Despite the opportunities afforded to them as strong donor countries to pursue joint approaches, Germany and France often tend to cooperate on an ad hoc basis rather than as part of a strategy (Krüger & Vaillé, 2019). Signed on 22 January 2019, the Aachen Treaty serves to renew the cooperation on Franco-German development cooperation (DC) formalised in the Élysée Treaty and offers the two countries a way to overcome differences and contribute jointly to global sustainable development (Aachen Treaty, Chapter 2, Article 7). Against this backdrop, this paper discusses challenges and opportunities for Franco-German DC based on two case studies in Cameroon and Morocco, which illustrate how differing mandates and methods being applied by the implementing organisations are preventing closer cooperation on the ground. Diverging political priorities, including within the national donor administrations, are also making it harder to engage in dialogue with the partner countries, especially if these have only limited capacity for donor coordination. If Germany and France succeed in overcoming their current differences, they will be able to attract other donors, particularly EU actors, for joint initiatives. Four policy recommendations can be derived from this: Improving coherence between DC systems: Even if the donor countries continue to maintain different political structures, the functional cooperation between the relevant actors will need to be supported at upper political levels. Coherence within the German and French DC systems should also be increased. 2. Germany and France should make it easier to launch joint projects: Programming cycles need to be better coordinated in the interests of the political dialogue on DC. At the same time, the mutual recognition of procedures that form part of both countries' technical cooperation (TC) and financial cooperation (FC) should be afforded greater political support. 3. Selecting partner countries and sectors strategically: Focusing on common priorities and sectors is advisable, especially in partner countries with limited capacity for coordination. Franco-German cooperation with middle-income countries should also be strengthened strategically in order to support projects requiring substantial financing in sectors such as renewable energy. 4. Structuring Franco-German cooperation so as to be open to other partners: Germany and France should commit to a common Europe-wide implementation approach and promote its application in partner countries through pilot projects. Franco-German DC should also be structured so as to be open to other actors and should campaign for the preservation of global public goods in international organisations in which both donors play an active part (e.g. in the Global Fund to Fight AIDS, Tuberculosis and Malaria).
Keywords: 330; Entwicklungshilfe; Deutsch; Französisch; Internationale Zusammenarbeit; Deutschland; Frankreich